A Cost‐Effective and Scaleable Approach for the In‐Situ Synthesis of Porous Carbon‐Coated Micrometer‐Sized AlSi Particles as Anode for Lithium‐Ion Batteries. Issue 9 (7th May 2019) - Li, Cheng; Li, Xitao; Zheng, Yan‐Zhen; Wu, Jiaojiao; Ding, Haiyang; Tao, Xia
Abstract: Silicon is intensively investigated as one of the most promising lithium‐ion battery anode material due to its high theoretical capacity. Here, spherical micro‐sized porous AlSi coated by a carbon layer (AlSi@C) are fabricated from low‐cost commercial AlSi alloy by delicately controlling an acid etching period, followed by polymerization and carbonization. A small amount of residual Al is beneficial to maintain the spherical morphology and enhance the electrical conductivity of the AlSi anode. Profiting from the porous structure and carbon coating layer, micro‐sized porous AlSi@C exhibits a high initial coulombic efficiency of 84.2 %, delivers an initial specific discharge capacity of 1650 mA h g −1 at a current density of 0.50 A g −1, and still retains 824 mA h g −1 after 300 cycles. This work provides a facile and scalable synthetic strategy for the preparation of porous Si‐based anode materials from low‐cost AlSi alloy, and it is expected to realize the industrialization of preparation of porous Si‐based anode materials. Abstract : Micron sized porous Aluminium/Silicon spheres coated with a carbon layer are fabricated from a low‐cost commercial AlSi alloy by delicately controlling the acid etching period, followed by polymerization and carbonization. When used as anode material for lithium‐ion batteries, the composite exhibits stable electrochemical performance.